Given that , radius of both the sphere and cylinder are same let V1 and V2 be the volume of the sphere and cylinder respectively.

Also given that V1=2/3 V2

for sphere r=(3V1 /4pi) the whole power 1/3

for cylinder r= √V2/pi*h

equating the radius

we get, (3V1/4pi) to the whole power 1/3 = √V2/pi*h .but V1=2/3 of V2

so replacing the V1 as 2/3V2

therefore (2*V2/4pi) to the whole power 1/3 =√V2/pi*h

Also given that V1=2/3 V2

for sphere r=(3V1 /4pi) the whole power 1/3

for cylinder r= √V2/pi*h

equating the radius

we get, (3V1/4pi) to the whole power 1/3 = √V2/pi*h .but V1=2/3 of V2

so replacing the V1 as 2/3V2

therefore (2*V2/4pi) to the whole power 1/3 =√V2/pi*h